Influence of Process Parameters and Convective Heat Transfer on Thermophysical Properties of SiO2 Nanofluids by Multiobjective Function Analysis (DFA). (27th January 2023) - Suprabha, R.; Mahesha, C. R.; Nanjundappa, C. E.
Abstract : From the requirements, high-performance cooling systems in the applications of solar, heat exchangers, and chemical industries are needed to improve efficiency. The metal-oxides-based nanofluids composed the better thermal properties with exchange of heat-transfer mechanisms. Therefore, this study mainly focused on nanosilicon dioxide materials to produce the nanofluids with blending of water-base medium by two-step techniques. The scanning electron microscope was used to analyze the presence of silicon dioxide nanoparticles from the procured material. During the two-step method input aspects like weight fraction of silicon dioxide (1.5–4.5 wt%), particle sizes (10–30 µ m), pH range of water (5–9), and sonication process time (2–4 hr) were considered. The outcomes like thermal conductivity, specific heat capacity, and viscosity were selected as thermal physical properties. The desirability techniques were implemented to identify the best optimal input parameters from the nanofluid processing. From the desirability outcomes, the processed nanosilicon dioxide fluids with respective input parameters were 0.9623 W/mK for thermal conductivity, 688 J/kg K forspecific heat capacity, and 0.00162 for viscosity, respectively. The heat-transfer coefficient was successfully identified with processed nanosilicon dioxide fluids, and the Nusselt number and Reynolds number were attained with respective heat-transfer coefficients.